2000
DOI: 10.4049/jimmunol.164.4.1814
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of IL-10-Related T Cell-Derived Inducible Factor (IL-TIF), a Novel Cytokine Structurally Related to IL-10 and Inducible by IL-9

Abstract: IL-9 is a Th2 cytokine active on various cell types such as T and B lymphocytes, mast cells, and eosinophils, and potentially involved in allergy and asthma. To understand better the molecular mechanisms underlying the activity of this cytokine, we used a cDNA subtraction method to identify genes specifically induced by IL-9 in mouse T cells. One of the IL-9-regulated genes isolated by this approach turned out to encode a 180-amino acid long protein, including a potential signal peptide, and showing 22% amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
336
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 446 publications
(348 citation statements)
references
References 21 publications
6
336
0
3
Order By: Relevance
“…IL-22 was originally identified as a gene induced by IL-9 in murine T lymphocytes. Stimulation of HepG2 human hepatoma cells with IL-22 up-regulated the production of acute phase reactants like serum amyloid A, ␣ 1 -antichymotrypsin, and haptoglobin (11,12). Expression of MDA-7 was up-regulated in wound healing and during the in vitro differentiation of a melanoma cell line (13,14).…”
Section: Il-19 Induces Production Of Il-6 and Tnf-␣ And Results Inmentioning
confidence: 99%
“…IL-22 was originally identified as a gene induced by IL-9 in murine T lymphocytes. Stimulation of HepG2 human hepatoma cells with IL-22 up-regulated the production of acute phase reactants like serum amyloid A, ␣ 1 -antichymotrypsin, and haptoglobin (11,12). Expression of MDA-7 was up-regulated in wound healing and during the in vitro differentiation of a melanoma cell line (13,14).…”
Section: Il-19 Induces Production Of Il-6 and Tnf-␣ And Results Inmentioning
confidence: 99%
“…In systemic diseases, it appears that IL-22 is primarily produced by T cells, most commonly Th1 and Th17 cells, with less expression from NK cells [10,14]. Research in reproductive tissues is not as definitive, but a few studies have identified uNK cells that are capable of expressing IL-22 [15].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ, a classical Th1 cell cytokine, is secreted by the CD4 + Th1 cells but also produced by CD8 + cytotoxic lymphocytes, natural killer cells (Young 1996), and professional antigen-presenting cells (Frucht et al 2001;Harris et al 2000). IL-22 is produced primarily by a subtype of CD4 + T cells, now known as Th17 cells (Dumoutier et al 2000a) while IL-26 mainly by various types of T cells (CD4, CD8, αβ, γδ; Knappe et al 2000). Many aspects of IFN-γ have been elucidated, including the important roles as a potent activator of macrophages and the key regulators in cell-mediated immunity (Schroder et al 2004).…”
Section: Discussionmentioning
confidence: 99%